Contribuições do entretenimento a bordo no conforto e desconforto em voos comerciais - Rossi, Talita Naiara (Universidade Federal de São Carlos, 2011)
The growth of passengers air transport as well as the competitiveness of the aviation industry have made the comfort a noticeable item to be taken into account, which is characterized as a key variable for the cabin project and also for the differentiation in the market, once it is related to the passengers satisfaction and acceptance when it comes to this transportation modality. In this context, the in-flight entertainment has been considered one of the most relevant requisite in order to improve the comfort while in the cabin in a way that it enhances values of the airline companies, contributing for a more pleasant and also a rather positive air travel experience. Thereby the aim of this study is to understand the aspects of either comfort or discomfort in airplane cabins, exchanging views on the importance of entertainment activities on board as well as their influence on comfort and discomfort in the cabin. Firstly, based on the literature review it made possible to clearly understand the concepts of comfort and discomfort including the current possibilities of in-flight entertainment. Considering comfort as an outstanding and suitable point to be applied in the cabin, this study is grounded in the approach of the analysis of the activity. As such, the data collection was implemented in two contexts: survey of Brazilian commercial aviation (airports and domestic flights) and interviews with companies connected with the entertainment industry and air transport sector. The procedures adopted have permitted to identify the active travellers preferences and expectations when it comes to in-flight entertainment, what is more, the constraints during the activities occurred in the cabin and tendency of the industry in question. Some recommendations for the project were made, highlighting, mainly, the importance of the amenities in the aircraft cabin for the travelers to use their own devices during the flight.
Keywords: Ergonomia; Aeronáutica comercial; Transportes - trânsito de passageiros; Aeronaves; Air transport; Passengers; Comfort/discomfort; In-flight entertainment; ENGENHARIAS::ENGENHARIA DE PRODUCAO